Detection and seroprevalence of Q fever infection in dairy goats in Besut district, Malaysia - Ahmad, Khairunnisa; Nik Mustaffa, Nik Danial Asyraf; Azmi, Nur Syafiqa; Zainal Ariffin, Siti Mariam; Ghazali, Mohd Faizal; Ibrahim, Noor Syaheera (Network for the Veterinarians of Bangladesh, 2024)
Objective: This study aimed to investigate the seroprevalence of Q fever and its association with age and gender among Saanen dairy goats in Malaysia. Material and Methods: One hundred dairy goats (n = 100) aged 6 months to 6 years were randomly selected, and blood samples were collected for serological analysis using the enzyme-linked immunosorbent assay technique. Results: The results revealed a seropositive rate of 70% among the goats, with medium-positive titers being the most common. The prevalence of Q fever varied among different age groups, with higher rates observed in adult goats aged between 5 and 6 years. Gender analysis showed that males had a higher positive rate (p < 0.05) of Q fever compared to females. Conclusion: These findings strongly indicate the presence of Coxiella burnetii in the dairy goat population and highlight the importance of implementing biosecurity measures and control strategies to prevent further transmission of this disease. This research has contributed to a better understanding of Q fever epidemiology and provides insights for effective control and prevention strategies in dairy goat populations.